Karawitan Composition Gending Tresna | Komposisi Karawitan Gending Tresna - Dewa Gede Rahma Adi Putra; I Nyoman Sudiana (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The creation of this musical is intended to express feelings of love for someone. Feeling is defined as a state that is felt is happening within a person. You experience feelings of anger, because you feel something stir within you. With this explanation, the author is very interested in raising the feeling that will be used as an innovative percussion composition. This composition will be titled “Gending Tresna” which is interpreted as a love song that tells the feelings of love for a pair of lovers. The creation method used is idea exploration, technique exploration, conception exploration, and the formation stage. The medium to express musical feelings is the Selonding gamelan plus several other instruments that can be poured into an innovative composition entitled Gending Tresna. The composition of this music is in the form of an innovative percussion by still using traditional patterns and considering the melody line in accordance with the atmosphere of the idea and concept of wholeness, balance, and prominence from the first part to part 3 in a structured, interrelated manner.